Diversified Cropping Modulates Microbial Communities and Greenhouse Gas Emissions by Enhancing Soil Nutrients - Zhongyan Wang; Huaqiang Xuan; Bei Liu; Hongfeng Zhang; Tongyan Zheng; Yunxia Liu; Luping Dai; Yi Xie; Xianchao Shang; Li Zhang; Long Yang; Sitakanta Pattanaik; et al. (Agronomy, 2025)
Crop diversification has been acknowledged as a means of lowering the environmental impact of agriculture without sacrificing agricultural output in recent years due to the growth of intensive agriculture. Crop rotation and intercropping—the methodical growing of two or more crops on one plot—are promising practices in this regard. Therefore, we conducted a quantitative bibliometric analysis of observed data between 2014 and 2024 to identify current research hotspots and future research trends in intercropping and crop rotation. A further secondary search for research advances in four key sub-areas (soil physicochemical properties, microbial diversity, greenhouse gas emissions (CO2, N2O, or CH4) and crop yield) was conducted based on keyword clustering. Our findings suggest that a crop diversification strategy can significantly increase soil nutrient content, optimize soil physicochemical properties, and regulate microbial community structure. In addition, this strategy can help to reduce greenhouse gas emissions (CO2, N2O, CH4), which will have a positive impact on the atmospheric environment. Crop diversification improves crop yield and quality, which in turn increases farmers’ economic returns. In order to maximize the effective production methods of crop rotation and intercropping, and to increase the efficiency of resource usage, this paper examines the development of research and practice on two cropping patterns worldwide.